Adapting cities for climate change through urban green infrastructure planning. (October 2021) - Ramyar, Reza; Ackerman, Aidan; Johnston, Douglas M.
Abstract: Green Infrastructure (GI) planning firstly developed as an integrated approach to ecological and conservation planning. Then it has advanced and used in several disciplines such as urban and reginal planning and landscape architecture. This diversity has promoted a range of planning initiatives and widespread its usage while make it difficult to define and operationalize GI planning. However, this is a planning strategy that has the potential to promote urban landscape planning by providing a holistic understanding of the dynamics of socio-ecological systems. GI planning, by producing a variety of ecosystem services, and having proactive multi-function and multi-discipline approach in planning, enhances our ability to deal with climate change in urban scale. Significant advances in GI planning have recently been made in integrating adaptation objectives in plans. However, in incorporating urban GI planning strategy to urban adaptive planning to cope with disasters, many challenges remained linked to integrate these two strategic planning in urban ecological planning with opportunistic response, more than only simple unintegrated defensive strategy. This research tries to take a step in this direction and seeks to investigate what constitutes GI as a strategy, and through this strategy how it can be possible to offer an integrated approach in urban planning practice. Then it investigates what are the key concepts and principles of urban adaptive planning, and how urban adaptive planning can be made operational in urban GI planning practice. In this essay, a transdisciplinary framework for adaptive urban GI planning is proposed to integrate science and professional practice. It includes adaptive strategies from climate change adaptation and ecological planning in a structured form to simultaneously support different type of responses in planning and improve transformability and flexibility in planning and practice. Highlights: GI planning is an integrated approach to ecological and conservation planning. GI planning enhances our ability to deal with climate change in various scales. Ecosystem multifunctionality is helpful to meet the challenges of adaptation. To operationalize GI adaptive, multi-function planning we need an integrated model.